2020
DOI: 10.29393/ce26-9cvdv50009
|View full text |Cite
|
Sign up to set email alerts
|

Calidad De Vida Laboral Y Estrategias De Mejora Del Trabajo De La Enfermería Docente

Abstract: Objective: To identify the occupational factors a ecting the quality of working life of nurse educators and design strategies to improve it. Material and Method: Descriptive, exploratory, qualitative study, developed with a focus on critical epidemiology, conducted at a nursing school in Chile. e research subjects corresponded to 17 nurse educators, who were given individual semi-structured interviews and 9 participated in a focus group. e research was approved by the Research Ethics Committee of the instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The tracking of qualitative antecedents on QWF of the HWF showed that those found converge with the quantitative reports, which indicates the need to carry out more research with integration of methods to provide elements to establish improvement strategies from the institutions and from the individual (30).…”
Section: Discussionmentioning
confidence: 89%
“…The tracking of qualitative antecedents on QWF of the HWF showed that those found converge with the quantitative reports, which indicates the need to carry out more research with integration of methods to provide elements to establish improvement strategies from the institutions and from the individual (30).…”
Section: Discussionmentioning
confidence: 89%
“…It is also one of the most important factors for the motivation and improvement of human resources (Royuela et al, 2009). Similarly, work determines social status and gives meaning to life (Parra-Giordano et al, 2020) and is still under constant study (Tonon de Toscano, 2009). In this sense, the objective of this research was to determine whether social support and GSE predict the quality of life at work for Ecuadorian teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Toscano-del Cairo et al (2020) affirmed that a healthy organization is one that is characterized by an environment of social and organizational support. Several studies reported that the lack of support can lead teachers to abandon the educational institution (Kuehn, 2010;Parra-Giordano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ambiente escolar foi avaliado pelos estudos como fator importante na análise do bem-estar do professor, mostrando-se pertinentes as avaliações das condições laborais para a prevenção de riscos e adoção de ações adequadas à proteção da saúde mental do docente e da qualidade de vida no trabalho (Biagi, 2017;Parra-Giordano, Felli, Fernández, Pinto-Gallegüillos, & Malabrigo, 2020;Romero-Caraballo, 2019; S. V. M. Santos et al, 2019). Os estudos, embora realizados em contextos diferentes, envolvendo pesquisas em países desenvolvidos ou em desenvolvimento com professores de escolas públicas e privadas, dos segmentos da Educação Básica (infantil, fundamental, médio e técnico) e da Educação Superior, o contexto escolar, apresentado de forma integral nos seus aspectos estrutural, cultural e social, foi descrito como capaz de interferir na percepção de bem-estar dos professores.…”
Section: Relações Entre Bem-estar Docente E Fatores Do Contexto Laboralunclassified